Enhancing the precision of continuum robots in orthopedic surgery based on mechanical principles - Pang, Tongtao; Liang, Jinkui; Lin, Zechen; Zhang, Xubin; Du, Finxin (Frontiers in Bioengineering and Biotechnology, 2024)
In the field of orthopedic surgery, the notched continuum robot has garnered significant attention due to its passive compliance, making it particularly suitable for procedures in complex and delicate bone and joint regions. However, accurately modeling the notched continuum robot remains a significant challenge. This paper proposes a high-precision mechanical modeling method for the notched continuum robot to address this issue. The flexible beam deflection prediction model based on the beam constraint model is established. The force balance friction model considering internal friction is established. An accurate static model is obtained, which can accurately estimate the deformation and deflection behavior of the robot according to the input driving force. The kinematic model of the notched continuum robot based on the static model is established. This method achieves high accuracy while ensuring computational efficiency. Experimental results demonstrate that the static model's error is only 0.1629 mm, which corresponds to 0.25% of the total length of the continuum robot, which is 66 mm. This research provides valuable insights into the modeling and control of continuum robots and holds significant implications for advancing precision in orthopedic surgery.